Research data governance activities for implementation in Malaysia research performing organizations: insights from data practitioners via Delphi study - Norzelatun Rodhiah Hazmi; Abrizah A.; A.M.K. Yanti Idaya (Malaysian Journal of Library and Information Science, 2023)
The rapid growth of research data and its influence on research practices has heightened global awareness of the significance of research data governance (RDG). However, there is a lack of literature explicitly outlining the implementation of RDG and the practices adopted by research performing organizations (RPOs). This study intends to bridge this gap by utilizing a three-round modified Delphi method, which involves a systematic solicitation and collection of feedback from a pool of experts comprising research data practitioners. This is accomplished through a series of carefully designed sequential surveys focused explicitly on RDG activities concerning tasks associated with governance roles, areas and decision domains within RPOs in Malaysia. The objective of this study is to develop consensus among research data practitioners on the importance of RDG activities. Statements were evaluated using a 5-point scale, and consensus was determined as an interquartile deviation (IQD) ≤ 0.5, a median ≥ 4, and a consensus level (CL) ≥ 85%. Analysis of the responses revealed a significant consensus among the experts on 106 out of 119 RDG task statements on various roles, nineteen areas, and eight decision domains deemed significant to the RDG implementation within RPOs. This study can potentially develop an RDG framework based on the consensus achieved. By providing an RDG framework that can be used as a set of best practices, this study can assist RPO leaders in considering implementing RDG and its efforts in their organizations.